Development of Starch-Polyvinyl Alcohol Films-based pH indicator for Detection of Penicillin G Residue in Raw Milk. Issue 1 (1st January 2022) - Saengdee, Pawasuth; Nuanthong, Thanin; Chamnan, Pomthip; Pattamang, Pattaraluck; Thongsook, Oraphan; Meananeatra, Rattanawan; Ranron, Norabadee; Pankong, Krynnaras; Uahchinkul, Warinrampai; Jeamsaksiri, Wutthinan; Vongkamjan, Kittiya; Chokboribal, Jaroenporn; et al.
Abstract: The detection of residual penicillin G (Pen G) in raw milk is very crucial to prevent the adverse effect from the allergy of Pen G to dairy consumer. However, the conventional detection methods require highly expensive instruments, high-skill technicians and complicated sample preparation process. In this research, a Lab-on-a-Disc (LOAD) to detect the residual Pen G in raw milk was introduced. The LOAD (ϕ: 9.0 cm) consisted of 10 micro-channels with the maximum volume of 200 μL was fabricated by laser machining of PMMA sheets. The 8.0 μm-thick polyvinyl alcohol, PVA (0.03125 % w/v) mixed with corn starch at a ratio of 3:7 (v/v) and bromocresol purple (BCP) pH indicator (0.025 % w/v) film that used as a Pen G indicator was prepared by hydrogel method and coated on the micro-channels by drop casting method. After the LOAD was rotated at 5000 rpm for 5 min at 25 °C, the BCP-(S-PVA) indicator film with the solubility of 93.56 % was dissolved in a raw milk mixed with Pen G (4.0 ng/mL) and the color of BCP-(S-PVA) film has changed from dark violet to light violet. The detection limit of BCP-(S-PVA) film to detect the Pen G in raw milk that obtained from the linear dose response curve (R 2 : 0.9630) is 0.17 ng/mL. Therefore, the LOAD with the BCP-(S-PVA) pH indicator is the fast and accurate promising method to determine the residual Pen G in raw milk at room temperature.